2016
DOI: 10.1186/s13014-016-0719-2
|View full text |Cite
|
Sign up to set email alerts
|

Prostate external beam radiotherapy combined with high-dose-rate brachytherapy: dose-volume parameters from deformably-registered plans correlate with late gastrointestinal complications

Abstract: Background: Derivation of dose-volume correlated with toxicity for multi-modal treatments can be difficult due to the perceived need for voxel-by-voxel dose accumulation. With data available for a single-institution cohort with long follow-up, an investigation was undertaken into rectal dose-volume effects for gastrointestinal toxicities after deformably-registering each phase of a combined external beam radiotherapy (EBRT)/high-dose-rate (HDR) brachytherapy prostate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
0
20
1
Order By: Relevance
“…Five studies had each reported a rectal DVH threshold for Rectal bleeding defined primarily as being moderate and requiring surgery/transfusion (N=647; Tables 3, S1, S2) [3539]. The five thresholds were located within 52–68Gy/2–12% [3537], and within 150–180Gy/2% [38, 39] No function was explored to fit these five thresholds given lack of data in between the two clusters of DVH thresholds (Fig S1). Thresholds for other GI toxicities included intermediate rectal thresholds at 25–58Gy/4–62% for occasional Anorectal pain , occasional Defecation Urgency , Diarrhea (increase in daily stools), and Stool frequency (4–8 times/day) [35] (N=118; Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies had each reported a rectal DVH threshold for Rectal bleeding defined primarily as being moderate and requiring surgery/transfusion (N=647; Tables 3, S1, S2) [3539]. The five thresholds were located within 52–68Gy/2–12% [3537], and within 150–180Gy/2% [38, 39] No function was explored to fit these five thresholds given lack of data in between the two clusters of DVH thresholds (Fig S1). Thresholds for other GI toxicities included intermediate rectal thresholds at 25–58Gy/4–62% for occasional Anorectal pain , occasional Defecation Urgency , Diarrhea (increase in daily stools), and Stool frequency (4–8 times/day) [35] (N=118; Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The five thresholds were located within 52–68Gy/2–12% [3537], and within 150–180Gy/2% [38, 39] No function was explored to fit these five thresholds given lack of data in between the two clusters of DVH thresholds (Fig S1). Thresholds for other GI toxicities included intermediate rectal thresholds at 25–58Gy/4–62% for occasional Anorectal pain , occasional Defecation Urgency , Diarrhea (increase in daily stools), and Stool frequency (4–8 times/day) [35] (N=118; Table 3). For Fistula , one threshold at 93Gy/2% (N=2368) was identified [40].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is common for retrospective studies, such as this one, to be constrained by resources and protocols in place at the time patients were treated. The potential influence of inter/intra‐fraction motion on rectum doses for patients in this study who received combined prostate EBRT/HDR‐BT has previously been discussed in more detail …”
Section: Discussionmentioning
confidence: 99%
“…Mixed results were seen depending on questions/ symptoms for age and T-stage. Patients’ symptoms and late effects following treatment may be linked to other factors not analyzed in this study such as treatment volume, dose received to critical structures including the rectum [ 28 ], patient weight, diet, and lifestyle factors. Further research is warranted to determine whether these factors impact on incidence and severity of symptoms reported by patients.…”
Section: Discussionmentioning
confidence: 99%